2015
DOI: 10.1063/1.4918291
|View full text |Cite
|
Sign up to set email alerts
|

A dedicated compression device for high resolution X-ray tomography of compressed gas diffusion layers

Abstract: We present an experimental approach to study the three-dimensional microstructure of gas diffusion layer (GDL) materials under realistic compression conditions. A dedicated compression device was designed that allows for synchrotron-tomographic investigation of circular samples under well-defined compression conditions. The tomographic data provide the experimental basis for stochastic modeling of nonwoven GDL materials. A plain compression tool is used to study the fiber courses in the material at different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Imaging techniques such as synchrotron X-ray imaging [44] and X-ray computed tomography [45] have been widely used to investigate the microstructural changes of GDL under clamping force. For example, Zenyuk et al [46] and Tötzke et al [47] utilized X-ray computed tomography (CT) to explore the microstructural change, such as porosity, tortuosity, and pore-size distribution (PSD) of different GDL materials under various levels of compression loads, concluding that the porosity decreased with compression and the PSD shifted from bimodal to unimodal while the larger pores were shifted to that of the smaller radii. Atkinson et al [48] investigated the variation of the porosity and ohmic resistance of different GDL types under varying degrees of compression on the influence of the mass transport resistance via X-ray CT and found that the concentration losses increased with compression owing to the decreased porosity.…”
Section: Deformation Of Porous Electrodementioning
confidence: 99%
“…Imaging techniques such as synchrotron X-ray imaging [44] and X-ray computed tomography [45] have been widely used to investigate the microstructural changes of GDL under clamping force. For example, Zenyuk et al [46] and Tötzke et al [47] utilized X-ray computed tomography (CT) to explore the microstructural change, such as porosity, tortuosity, and pore-size distribution (PSD) of different GDL materials under various levels of compression loads, concluding that the porosity decreased with compression and the PSD shifted from bimodal to unimodal while the larger pores were shifted to that of the smaller radii. Atkinson et al [48] investigated the variation of the porosity and ohmic resistance of different GDL types under varying degrees of compression on the influence of the mass transport resistance via X-ray CT and found that the concentration losses increased with compression owing to the decreased porosity.…”
Section: Deformation Of Porous Electrodementioning
confidence: 99%
“…Our numerical results are in good agreement with the experimental observations reported in some papers. 7,8 Figure 8 shows the displacement distributions in three different directions for the FPM and FFPM cases at CR = 20%. As can be seen in Fig.…”
Section: Displacement Distribution Of Compressed Gdls-we Next In-mentioning
confidence: 99%
“…In the past decade, techniques including the X-ray computed tomography (XCT), 6,7 optical microscope, 8 scanning electron microscope (SEM) 9,10 and other optical methods have been employed to observe the microstructural change of the inhomogeneous, compressed porous media. For the XCT technique, GDL samples were scanned at 1-2 μm/pixel resolution, and the two-dimensional images acquired were then used to reconstruct three-dimensional GDL models.…”
mentioning
confidence: 99%